DETERMINATION OF BISPHENOL A IN BEVERAGES BY RP-HPLC - Biljana PETANOVSKA-ILIEVSKA, Mirjana S. JANKULOVSKA, Lenche VELKOSKA-MARKOVSKA, Jasmina SPASOVSKA (Biotechnical Faculty of the University of Montenegro, 2019)
Bisphenol A (BPA) is a monomer widely used in the production of polycarbonate, epoxy resins, diacrylates and phenolic resins. A small quantity of BPA can migrate into the food and thus it can be potential hazard for human health and environment. Therefore, quantitative determination of BPA is of a great importance. A fast, simple, precise and economic RP-HPLC method with UV-DAD detection for quantitative determination of BPA in beverages was developed. Three different analytical columns were tested: Hypersil ODS (250 mm x 4.6 mm; 5 µm), LiChrospher 60 RP-Select B (125 mm x 4 mm; 5 µm) and Purospher® STAR RP-18 endcapped (30 mm x 4 mm; 3 µm). Analyzed beverages were packed in plastic bottles and small glass bottles closed with a cops coated with epoxy resin on inside. For quantitative determination of BPA following experimental conditions were established: mobile phase consisted of acetonitrile/water 50/50 (v/v), flow rate of 1 mL/min, column temperature of 25 oС, injection volume of 5 µL and UV detection at 200 nm. The method was developed in an isocratic manner and with a reversed phase column. Prior the analyses the samples were filtrated through syringe filters Spartan – T with pore size 0.45 µm. The following parameters were determined: retention time, linearity, limit of detection (LOD), limit of quantification (LOQ), precision, accuracy, selectivity and sensitivity. The RP-HPLC method with UV-DAD detection can be successfully used for quantitative determination of BPA in non alcoholic beverages without pre-treatment. The BPA was not detected in the analyzed beverages.
Keywords: Bisphenol A, RP-HPLC, UV-DAD detection, non-alcoholic beverages.